Hubungan Antara Faktor Sosioekonomi dengan Kejadian Stunting pada Balita di Cimahi Tengah - Dhania Dwintantika; Ratna Dewi Indi Astuti; Siti Annisa Devi Trusda (Bandung Conference Series: Medical Science, 2024)
Abstract. Toddlers are short if the z-score is below -2SD and very short if -3SD. Central Cimahi District is the area with the largest stunting rate in the city of Cimahi. The purpose of the study was to determine the relationship between socioeconomic factors and the incidence of stunting in toddlers in Central Cimahi. This study is a quantitative study, with observational analytical methods using a comparative cross sectional design. The number of samples was 30 for cases and 30 for control using a 2-proportion difference test taken through purposive sampling. Data was taken by giving a questionnaire containing 18 questions. Research site at Posyandu Karang Mekar in March – November 2023. Inclusion criteria included families with children younger than 5 years old and parents willing to be the subjects of the study. Exclusion criteria include children who have disorders such as congenital defects in organs and children who have chronic diseases. Data analysis of this study used Chi-square. The results showed maternal education (p=0.033), father's job (p=0.037), mother's job (p=0.020), father's income (p=0.015), and mother's income (p=0.021). In conclusion, there is a relationship between the mother's education level, father's job, mother's job, father's income and mother's income with the incidence of stunting in Central Cimahi. Family socioeconomic factors have an important role in the incidence of stunting. Abstrak. Balita pendek jika z-score di bawah -2SD dan sangat pendek jika -3SD. Kecamatan Cimahi Tengah merupakan daerah dengan angka stunting terbesar di kota Cimahi. Tujuan penelitian untuk mengetahui hubungan antara faktor sosioekonomi dengan kejadian stunting pada balita di Cimahi Tengah. Penelitian ini merupakan penelitian kuantitatif, dengan metode analitik observasional menggunakan desain cross sectional comparative. Jumlah sampel sebanyak 30 untuk kasus dan 30 untuk kontrol menggunakan uji beda 2 proporsi yang diambil melalui purposive sampling. Data diambil dengan cara memberikan kuesioner berisi 18 pertanyaan. Tempat penelitian di Posyandu Karang Mekar pada bulan Maret – November 2023. Kriteria inklusi meliputi keluarga yang memiliki anak berusia kurang dari 5 tahun dan orangtua yang bersedia menjadi subjek penelitian. Kriteria eksklusi meliputi anak yang memiliki kelainan seperti cacat bawaan pada organ tubuh dan anak yang memiliki penyakit kronis. Analisis data penelitian ini menggunakan Chi-square. Hasil penelitian menunjukkan pendidikan ibu (p=0,033), pekerjaan ayah (p=0,037), pekerjaan ibu (p=0,020), pendapatan ayah (p=0,015), dan pendapatan ibu (p=0,021). Simpulan, terdapat hubungan antara tingkat pendidikan ibu, pekerjaan ayah, pekerjaan ibu, pendapatan ayah dan pendapatan ibu dengan kejadian stunting di Cimahi Tengah. Faktor sosioekonomi keluarga memiliki peran peran penting terhadap kejadian stunting.